PROSPEK USAHA AGROINDUSTRI KOPI DI DESA JATI BARU KECAMATAN ASTAMBUL KABUPATEN BANJAR - Eddy Triatmoko; Subhan Fitriadi; Abdul Gafur (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The purpose of this research is to know the revenue,the total cost and the income of  coffee agroindustri bussiness . This research was conducted in Januari to Februari 2016 at Jati Baru village Astambul  Banjar . The sensus metode used was by observing 7 craftsmen in Jati Baru village who see about Coffee agroindustri bussiness . The Average result of the revenue is Rp. 7.136.000,/ craftsmen, the average variabel cost is Rp.5.682.500/craftsmen and the average fixed cost is Rp. 95.000/craftsmen,  the average total cost  is Rp.5.739.300/craftsmen, and the average income is Rp. 1.396.000/craftsmen. From  this result of development of coffee agroindustri bussiness we believe that it has good prospect and revenue,tecnically and economically.